Project-based-learning on critical reading course to enhance critical thinking skills - Dina Merris Maya Sari; Yudy Prasetyo (Studies in English Language and Education, 2021)
In some cases, EFL (English as a Foreign Language) students may be lack critical thinking in reading, particularly in Indonesia. The purposes of this study were to investigate the implementation of Project-Based-Learning (PjBL) on critical reading to enhance critical thinking skills and describe the students’ responses on the implementation of PjBL in critical reading to enhance critical thinking skills. This research employed a mixed-method approach. The subjects of this research were 26 EFL students at STKIP PGRI Sidoarjo, Indonesia. The data were obtained by using observation, interviews, and questionnaires. Data analysis techniques included data reduction, data presentation, and data conclusion. This study produced several results. Firstly, the implementation of PjBL on critical reading course to enhance critical thinking skills consisted of three stages: 1) planning, 2) implementing, and 3) evaluating. Secondly, based on the interviews, 88.89% of the students were motivated in working on the assignments by using the PjBL model, and 54% of them were excellent. Thirdly, based on the questionnaire, most students (73%) chose “strongly agree” with critical thinking skills. It is hoped that the findings of this research can give information about students’ critical thinking and give an appropriate learning model to enhance the students’ critical thinking.